Rapid Isolation of High Molecular Weight Urokinase from Native Human Urine - Huber, Kurt; Kirchheimer, Johannes; Binder, Bernd R (Thrombosis and Haemostasis, 1982)
Urokinase (UK) could be purified to apparent homogeneity starting from crude urine by sequential adsorption and elution of the enzyme to gelatine-Sepharose and agmatine-Sepharose followed by gel filtration on Sephadex G-150. The purified product exhibited characteristics of the high molecular weight urokinase (HMW-UK) but did contain two distinct entities, one of which exhibited a two chain structure as reported for the HMW-UK while the other one exhibited an apparent single chain structure. The purification described is rapid and simple and results in an enzyme with probably no major alterations. Yields are high enough to obtain purified enzymes for characterization of UK from individual donors.
Keywords: Urokinase; HMW-urokinase; Native urine; Plasminogen activator; Activity; Gelatine-Sepharose